The influence of environmental risk factors in the development of ALS in the Mediterranean Island of Cyprus - Mitsi, Ellie; Christodoulou, Christiana C.; Nicolaou, Paschalis; Christodoulou, Kyproula; Zamba-Papanicolaou, Eleni (Frontiers in Neurology, 2023)
Introduction Amyotrophic lateral sclerosis (ALS) is a devastating, uniformly lethal degenerative disease of motor neurons, presenting with relentlessly progressive muscle atrophy and weakness. The etiology of ALS remains unexplained for over 85% of all cases, suggesting that besides the genetic basis of the disease, various environmental factors are implicated in the pathogenesis of ALS. This study aimed to investigate the contribution of known environmental risk factors of ALS in the Cypriot population. Methods We conducted a case–control study with a total of 56 ALS cases and 56 healthy gender/age-matched controls of Cypriot nationality. Demographic, lifestyle characteristics, medical conditions, and environmental exposures were collected through the use of a detailed questionnaire. Statistical analyses using the R programming language examined the association between the above environmental factors and ALS. Results A chi-square test analysis revealed a statistically significant (p = 0.000461) difference in smoking status between the two groups. In addition, univariate logistic regression analysis showed a statistically significant association between ALS cases for head trauma/injury (p = 0.0398) and exposure to chemicals (p = 0.00128), compared to controls. Conclusion This case–control investigation has shed some light on the epidemiological data of ALS in Cyprus, by identifying environmental determinants of ALS, such as smoking, head trauma, and chemical exposure, in the Cypriot population.